Faktor-faktor yang Mempengaruhi Pelaksanaan Inisiasi Menyusu Dini di Instalasi Kamar Bedah Rumah Sakit Panti Rapih Yogyakarta - Mahdalena Diyah Pujiastuti, Maria; Mahayanti, Agnes; Maura Hardjanti, CB, Sr. Therese (STIKes Panti Rapih, 2021)
ABSTRACT Background: The success of breastfeeding is a team work with proper information and big support to create environment enabled the mothers to give breastfeeding optimally to their baby (Kemenkes, 2019). Keeping in mind that the OT achievement is far below 100% , the researcher is interested in take up factors influence the application of Early Initiation of Breastfeedingin Operating Theater Unit of Panti Rapih Hospital Yogyakarta. Objective: Unveil factors wish interfere the practice of Early Initiation of Breastfeeding in Operating Theater Unit of Panti Rapih Hospital Yogyakarta. Methods: The design of the study is observational analytic method with cross sectional approach. The population of the study is every mother who gives birth with sectio caesarea in Operating Theater Unit of Panti Rapih Hospital Yogyakarta. Sampling technique in the study is accidental sampling. This study had 33 respondents. Study instrument in the study is questionnairefilled out by respondents on the first day after sectio caesarea was performed in the inpatient room. The research was conducted from September 2020 to February 2021. Results: There is no significant correlation between knowledge and IMD practice (p value 0.772), there is no significant correlation between attitudes and IMD practice ( p value 0.500), there is no significant correlation between parity and IMD practice (p value 0.500), there is a significant correlation , strong and unidirectional between health personnel support and IMD practice (p value 0.000) . Conclusion: Significant factors interfere with the success of Early Initiation of breastfeeding in the Operating Theater Unit of Panti Rapih Hospital Yogyakarta is health personnel supportwhile the insignificant factors consists of knowledge, attitude and parity.